Analisis Maqasid Al-Syariah menurut Imam Al-Ghazali tentang Konsep Kebutuhan dan Keinginan dalam Masyarakat - Aqidatul Izza; Intan Tri Nuraini; M. Aviek Ulul Amwal; Sri Wigati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This study aims to analyze the concept of needs and wants in modern society through the perspective of Maqasid al-Syariah according to Imam al-Ghazali. The rapidly growing consumerist and materialistic phenomenon due to globalization, digital technology, and hedonistic culture has caused a shift in consumption priorities so that the boundaries between needs and wants have become blurred. Through a qualitative research method based on literature studies, this study examines al-Ghazali's thoughts on al-daruriyyat al-khams and the categorization of human needs which include dharuriyyah, hajiyyah, and tahsiniyyah. The results show that the concept of maqasid formulated by al-Ghazali provides an ethical and normative framework that can direct people's consumption patterns to align with the principles of benefit, moderation, and material-spiritual balance. These findings also confirm that the application of maqasid values can be a solution to various negative impacts of modern consumerism, such as wasteful behavior, social inequality, and moral degradation. This study concludes that Maqasid al-Syariah is relevant as an ethical guideline in building proportional and civilized consumption behavior in the contemporary era.